PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Astrinita, Elda; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to test partially and simultaneously the effect of liquidity and leverage on the firm's value on banks listed on the Indonesia Stock Exchange. Where the independent variable in this study is liquidity and leverage, while the dependent variable in this study is the value of the company. The method used to observe the effect of liquidity and leverage on the value of the company using simple linear regression and multiple linear regression. The data used in this study are secondary data, financial reports and annual report annual reports. The data is listed on the Indonesia Stock Exchange (IDX) for 5 years from the period 2012-2016. Sampling was done by purposive sampling, which used were 7 companies. Data analysis using simple linear regression, multiple linear regression, t test, f test and test coefficient of determination. Data analysis using simple linear regression and multiple linear regression with SPSS 16. The results of this study indicate that the variable liquidity partially (t test) does not affect the value of the company, while the leverage variable does not affect the firm value of banks listed on the Indonesia Stock Exchange. The simultaneous test results (F) show no effect of liquidity and leverage on the value of the company in banks listed on the Indonesia Stock Exchange.    Keywords: Liquidity, Leverage, Company Value